Perception of Benefit and Barrier of Staff Education's Faculty of Medicine, Public Health and Nursing Gadjah Mada University with the Intention the Support toward Health Promoting University - Harnianti; Yayi Suryo Prabandari; Nur Juliana (Journal of sciences and health, 2021)
Baground: Health promoting university (HPU) is a place to create a context of promoting health that is common in universities. This research aims to know the general picture of perception of education personnel FK-KMK UGM about the development of health promoting university. Method:This type of research is quantitative with cross sectional study design. Bivariate analysis of research results using chi square and multivariate using logistic regression. Results: The benefits of HPU according to tendik is to have policies relevant to the development of HPU, namely the prohibition of smoking, the availability of access to clean drinking water, the availability of bicycle routes to support physical activity, the environment supports physical activity, the availability of healthy canteens. HpU barriers according to tendik, namely the number of unhealthy foods and KTR policy has not been effective. Tendik FK-KMK UGM has a high intention to support the development of HPU. There is a significant relationship between benefits, with the intention of supporting the development of HPU with a value of p = 0.00. There is a significant relationship between obstacles and the intention of supporting the development of HPU with a value of p = 0.005. Conclusions:The perception of FK-KMK UGM education staff about hpu development requires a domain of improvement on less effective policy barriers and facilities on campus are underutilized. Keywords: health-promoting university, perceptions, benefits, barriers, intentions, education staff Pendahuluan: Health promoting university (HPU) adalah tempat untuk menciptakan konteks mempromosikan kesehatan yang bersifat umum di universitas. penelitian ini bertujuan mengetahui gambaran umum persepsi tenaga kependidikan FK-KMK UGM tentang pengembangan health promoting university. Metode: Jenis penelitian adalah kuantitatif dengan rancangan cross sectional study. Analisis hasil penelitian secara bivariat menggunakan chi square dan multivariat menggunakan regresi logistik. Hasil: Manfaat HPU menurut tendik adalah memiliki kebijakan yang relevan dengan pengembangan HPU, yaitu larangan merokok, tersedianya akses air minum bersih, tersedianya rute sepeda untuk penunjang aktivitas fisik, lingkungan mendukung aktivitas fisik, tersedianya kantin sehat. Hambatan HPU menurut tendik, yaitu masih banyaknya makanan tidak sehat dan kebijakan KTR belum efektif. Tendik FK-KMK UGM memiliki intensi yang tinggi mendukung pengembangan HPU. Terdapat hubungan yang signifikan antara manfaat, dengan intensi mendukung pengembangan HPU dengan nilai p = 0.00. Terdapat hubungan yang signifikan antara hambatan dengan intensi mendukung pengembangan HPU dengan nilai p = 0.005. Kesimpulan: Persepsi tenaga kependidikan FK-KMK UGM tentang pengembangan HPU membutuhkan domain perbaikan pada hambatan kebijakan yang kurang efektif dan fasilitas yang ada di kampus kurang dimanfaatkan. Kata kunci: health promoting university, persepsi, manfaat, hambatan, intensi, tenaga kependidikan